Weight-Loss Interventions for Hispanic Populations: The Role of Culture - Nangel M. Lindberg; Victor J. Stevens; Ruben O. Halperin (Journal of Obesity)
In the United States, ethnic minorities are overrepresented among the overweight and obese population, with Hispanic individuals being among the groups most at risk for obesity and obesity-related disease and disability. Most weight-loss interventions designed for the general population have been less successful with individuals from ethnic minorities and there is a pressing need to develop more effective interventions for these groups. This paper examines the importance of culture in the development of “culturally competent” weight-loss interventions for ethnic minority populations, and discusses specific culturally mediated factors that should be considered in the design and implementation of treatment interventions. While specifically focusing on Hispanic populations, we also address issues of relevance to other multiethnic societies.